In Vitro Evaluation of Probiotic Properties of Lactic Acid Bacteria Isolated from Some Traditionally Fermented Ethiopian Food Products - Guesh Mulaw; Tesfaye Sisay Tessema; Diriba Muleta; Anteneh Tesfaye (International Journal of Microbiology)
Probiotics are live microorganisms which when consumed in large number together with a food promote the health of the consumer. The aim of this study was to evaluate in vitro probiotic properties of lactic acid bacteria (LAB) isolated from traditional Ethiopian fermented Teff injera dough, Ergo, and Kocho products. A total of 90 LAB were isolated, of which 4 (4.44%) isolates showed 45.35–97.11% and 38.40–90.49% survival rates at pH values (2, 2.5, and 3) for 3 and 6 h, in that order. The four acid-tolerant isolates were found tolerant to 0.3% bile salt for 24 h with 91.37 to 97.22% rate of survival. The acid-and-bile salt-tolerant LAB isolates were found inhibiting some food-borne test pathogenic bacteria to varying degrees. All acid-and-bile-tolerant isolates displayed varying sensitivity to different antibiotics. The in vitro adherence to stainless steel plates of the 4 screened probiotic LAB isolates were ranged from 32.75 to 36.30% adhesion rate. The four efficient probiotic LAB isolates that belonged to Lactobacillus species were identified to the strain level using 16S rDNA gene sequence comparisons and, namely, were Lactobacillus plantarum strain CIP 103151, Lactobacillus paracasei subsp. tolerans strain NBRC 15906, Lactobacillus paracasei strain NBRC 15889, and Lactobacillus plantarum strain JCM 1149. The four Lactobacillus strains were found to be potentially useful to produce probiotic products.